2020 IEEE International Conference on Multimedia &Amp; Expo Workshops (ICMEW) 2020
DOI: 10.1109/icmew46912.2020.9106029
|View full text |Cite
|
Sign up to set email alerts
|

HMM-Based Framework to Measure the Visual Fidelity of Tone Mapping Operators

Abstract: Recent advancements in the image capturing techniques and post processing software generate High Dynamic Range (HDR) images. Such images retain maximum information of the scene by capturing more realistic visual contents, which are often missed in traditional image capturing techniques. In this regard, tone mapping operators (TMOs) play a significant role in displaying HDR image contents on a traditional Low Dynamic Range (LDR) display. These operators tend to introduce artifacts in the original HDR image to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the study of Ellahi et al (2020), the hidden Markov model (HMM) as a test of similarity to assess TMO perceived quality is proposed. The findings suggest that the proposed HMM-based method that emphasizes temporal information yields better evaluation metrics than traditional approaches based solely on visual-spatial information.…”
Section: Full-reference Modelmentioning
confidence: 99%
“…In the study of Ellahi et al (2020), the hidden Markov model (HMM) as a test of similarity to assess TMO perceived quality is proposed. The findings suggest that the proposed HMM-based method that emphasizes temporal information yields better evaluation metrics than traditional approaches based solely on visual-spatial information.…”
Section: Full-reference Modelmentioning
confidence: 99%
“…1) Visual attention similarity: As it has been shown that TMOs can impact both visual saliency and visual behavior in images, different similarity metrics based either on the comparison of saliency maps [14], either on the comparison of scanpaths in two tone-mapped images [15] are used.…”
Section: B Visual Attention Featuresmentioning
confidence: 99%
“…This metric is based on a HMM-based framework to measure the similarity of visual behavior between two conditions of experiment [15]. This method uses a HMM to model the sequence of eye movements of one observer [20], [21].…”
Section: Fixation Clusters Based Hidden Markov Model (Fchmm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tone mapping consists in the compression of the dynamic range of an image to match the characteristics of the displays, preserving the aesthetic visual quality of the represented scene and the artistic intention. Previous works based on ET experiments showed that tone mapping operators can significantly impact the fixation behavior highlighting the strong effect on contrast in VA [12]. For these reasons, tone mapping is a good representative use case of QoE applications.…”
Section: Introduction and Related Workmentioning
confidence: 99%